The biology, habits and food plants of the whitegrub Macrodactylus near ovaticollis (Coleoptera: Scarabaeidae) - BUENO, JUAN MIGUEL; RAMÍREZ, DARÍO; CARDONA, CÉSAR (Revista Colombiana de Entomología, 1998)
The whitegrub Macroda-ctylus near ovaticollis Bates (Coleoptera: Melolonthidae) has become an important pest of maize and other crops in the northeastern region of the Cauca Department in southwestern Colombia. Populations of this insect have increased steadily for the past five years in hillside areas, from 1,500 m (near the Salvajina dam) to 2,200 m in the Cabuyal watershed. Larvae feed on roots of grasses and wild plants, causing no apparent economic damage. Adults devour maize inflorescences causing severe damage to this crop. They also attack flowers of beans, mango, avocado, star apple, guamo, roses, hibiscus, me, sage, shepherd’s needle, and persimmon fruits. The biology of this insect was studied in a rearing chamber (21° C, 70% R.H., 12-hour photoperiod). The duration in days of the immature stages was as follows: egg, 19.5 ± 0.7; first instar, 51.5 ± 0.7; second instar, 59.1 ± 4.4; third instar, 193.5 ± 6.3; prepupa, 1.3 ± 0.5; pupa, 17.0 ± 1.9. The total duration from egg to adult emergence was estimated as 342.0 ± 14.6 days. The longevities of males and females were almost identical: 53.1 ± 6.7 days. Sex ratios were 1:1. After a preoviposition period that lasted 16.5 ± 4.3 days, females laid an average of 122.7 ± 11.9 eggs in an average oviposition period of 35.2 ± 5.7 days. Egg fertility was 96%. Habits and phenological aspects are described. Observations were made on the almost perfect synchronization between the phenology of the insect and that of the main host plants which allow the adults to emerge when most host plants are in full flowering.